Influence of Parameters of Railway Track Construction on Vertical Dynamic Interaction Vehicle/Track - Libor Izvolt; Jan Kardos (Communications - Scientific letters of the University of Zilina, 2011)
By analysing the dynamic interaction between the railway vehicle and the track we are able to explain complex interactive phenomena that are particularly important in the case of higher and high speed of a moving rail vehicle on railway track.The paper focuses on the solution of the above mentioned problem with the help of numerical computer simulations. The important step on the way to create a respective simulation model is setting objective entry parameters of railway track as well as taking its imperfections into consideration. These imperfections significantly influence the results of dynamic interaction. Out of the considered track imperfections, we particularly solve deformation resistance inhomogeneity of track grid subgrade and vertical irregularities of rail belt.